A A Grammatical Aspects of Song Lyrics “As It Was” by Harry Styles (A Discourse Analysis) - Silonita, Refina; Widyahening, Ch Evy Tri; Sumardiono, Sumardiono (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyze the grammatical aspects of song lyrics “As It Was” by Harry Styles using Halliday and Hasan’s (1976) discourse analysis theory. The study employed a qualitative descriptive method with the lyrics as the primary data. The analysis focused on grammatical cohesion, namely 1) Reference, 2) Substitution, 3) Ellipsis, and 4) Conjunction. The results show that the lyrics are dominated by personal reference such as “you” (11 times) and “it” (21 times), which construct intimacy and emphasis on emotional conditions. Demonstrative reference such as “this” and “that” highlight the contrast between past and present situations. Comparative reference with the word “same” (7 times) strengthens the theme of inevitable change. Ellipsis appears through contractions like